Vanadium‐based metal‐organic frameworks and their derivatives for electrochemical energy conversion and storage. Issue 3 (2nd February 2022) - Zhu, Jing; Chen, Xiaoyu; Thang, Ai Qin; Li, Fei‐Long; Chen, Dong; Geng, Hongbo; Rui, Xianhong; Yan, Qingyu
Abstract: With the excessive consumption of nonrenewable resources, the exploration of effective and durable materials is highly sought after in the field of sustainable energy conversion and storage system. In this aspect, metal‐organic frameworks (MOFs) are a new class of crystalline porous organic‐inorganic hybrid materials. MOFs have recently been gaining traction in energy‐related fields. Owing to the coordination flexibility and multiple accessible oxidation states of vanadium ions or clusters, vanadium‐MOFs (V‐MOFs) possess unique structural characteristics and satisfactory electrochemical properties. Furthermore, V‐MOFs‐derived materials also exhibit superior electrical conductivity and stability when used as electrocatalysts and electrode materials. This review summarizes the research progress of V‐MOFs (inclusive of pristine V‐MOFs, V/M‐MOFs, and POV‐based MOFs) and their derivatives (vanadium oxides, carbon‐coated vanadium oxide, vanadium phosphate, vanadate, and other vanadium doped nanomaterials) in electrochemical energy conversion (water splitting, oxygen reduction reaction) and energy storage (supercapacitor, rechargeable battery). Future possibilities and challenges for V‐MOFs and their derivatives in terms of design and synthesis are discussed. Lastly, their applications in energy‐related fields are also highlighted. Abstract : Emerging metal‐organic framework‐based materials are widely used in energy‐related applications due to their structural and compositional advantages. This review discusses the research progress of V‐MOFs (the pristine V‐MOFs, V/M‐MOFs, and POV‐based MOFs) and their derivatives (vanadium oxides, carbon‐coated vanadium oxide, vanadium phosphate, vanadate) for electrochemical energy conversion and storage, focusing on electrolytic water, supercapacitors and metal‐ion batteries, and prospects for future research directions.